Wireless Charging Control Strategy of Electric Vehicle Using Compensating Network - Yaya Wang, Yajuan Jia (Forest Chemicals Review, 1970)
This thesis aims to increase the charging distance and improve the charging efficiency of electric vehicles. The wireless charging control strategy of electric vehicles is studied by using the principle of magneto-fluid mechanics and magnetic resonance coupling wireless power transfer (MRC-WPT) system. First, the calculation method of coil parameters of four-coil MRC-WPT system is proposed, and the transmission characteristics of four-coil MRC-WPT system are analyzed, including the output voltage gain, input current gain, output power and transmission efficiency of traditional Serial-Serial-Serial-Serial (SSSS) compensating network. Then, Inductor-Capacitor-Capacitor (LCC) compensating network is introduced into the driving coil side to form a four-coil MRC-WPT structure of Inductor-Capacitor-Capacitor-Serial-Serial-Serial (LCC-SSS) compensating network. Then, the formed network is analyzed. The experimental platform is built to collect the input voltage, output voltage and other data of the system under the SSSS compensating network and LCC-SSS compensating network when the output voltage of the driving coil is 50V and the inductance coefficient is 0.5. The results reveal that when the inductance coefficient is 0.5, the maximum output power of LCC-SSS compensating network can reach 85W, while that of SSSS compensating network is only 10W. This is because there are no energy consuming components in the wireless charging system based on LCC-SSS compensation network. Through the combination of passive components, the energy in the system is stored in the resonant element without input series resistance, which increases the voltage acting on the driving coil, increases the input current flowing through the system, and improves the output power of the system. Finally, the curve is drawn to verify that the MRC-WPT system based on LCC-SSS compensating network can effectively improve the scientificity and feasibility of system transmission efficiency. This thesis has certain reference significance for the compensating network optimization of electric vehicle wireless charging system.